The Influence of Guru Penggerak Education and Teacher’s Discipline on the Quality of Primary School Learning (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to determine the significance of the influence of Guru Penggerak education and teacher discipline on the quality of learning of elementary school learning in Pedamaran District. This type of research is descriptive quantitative. The sample in this study consisted of 58 respondents with data collection techniques in the form of a questionnaire. The results of the research show that: 1) there is a significant influence of the Guru Penggerak education program on the quality of learning; 2) there is a significant influence between teacher discipline and the quality of learning; and 3) there is a significant influence between Guru Penggerak education programs and scientific disciplines on the quality of learning. This article contributes to the primary school teachers in Indonesia, to give chance and support the teachers to be Guru Penggerak and have discipline personality.